A comparative study on effects of intrathecal ropivacaine plus dexmedetomidine versus ropivacaine plus clonidine - Kujur, Shweta; Arora, K. K.; Murthy, Madhumita G.; Ekka, Jyoti Prakash Samuel (International Journal of Research in Medical Sciences, 2017)
Background: Subarachnoid block is a safe and effective alternative to general anaesthesia when surgical site is located on the lower extremities, perineum or lower body wall. Spinal anaesthesia produces intense sensory and motor blockade as well as sympathetic blockade. Intrathecal α-2-agonists are used as adjuvant drugs to local anaesthetics successfully over the last decade .They potentiate the effect of local anaesthetic and decrease the required doses. Clonidine is a partial α-2-adrenorecptor agonist used intrathecally, with a well- established record of efficacy and safety. Its addition to local anaesthetics prolongs the duration of both motor and sensory spinal blockade. Dexmedetomidine is an α-2-adrenorecptor agonist. It has α-2/α1 selectivity ratio which is eight times higher than that of Clonidine. With this background, this study was conducted to compare the effects of intrathecal Ropivacaine plus Dexmedetomidine versus Ropivacaine plus Clonidine during procedures. Methods: The present prospective study was carried out in the Department of Anaesthesiology, M.G.M. Medical College and M.Y. Hospital, Indore (M.P.), India. Study period was from June 2011 to July 2012. Patient were randomly allocated to one of the following three group in a double blinded fashion based on computer generated code: Ropivacaine (R), Ropivacaine + Dexmedetomidine (D); Ropivacaine + Clonidine (C). Nominal categorical data between study groups were compared using the Chi – squared test or Fisher’s exact test as appropriate. p<0.05 was considered to be significant. Results: In all age groups patients were equally distributed in three Groups. Mean time taken for the onset of sensory and motor block was quite low in group D patients. Thereby showing statistically highly significant difference in onset of sensory and motor blocks (P<0.001). Whereas mean duration of sensory and motor block was also quite prolonged in group D patients. (p<0.001) There is significant difference between all the three groups. Conclusion: In conclusion our study shows that intrathecal Dexmedetomidine or Clonidine added with isobaric Ropivacaine produces rapid and prolonged sensory and motor block as compared to plain Ropivacaine.